2015
DOI: 10.1177/0021998315588623
|View full text |Cite
|
Sign up to set email alerts
|

Influence of micro and nanofillers on mechanical properties of pultruded unidirectional glass fiber reinforced epoxy composite systems

Abstract: This paper reports, fabrication and characterization of unidirectional glass fiber reinforced epoxy composite filled with nano-size alumina, silica and micron-size alumina trihydrate fillers using pultrusion technique. Tensile, flexural and impact strengths were determined to evaluate the effectiveness of fillers on the mechanical properties. Results show that the micro and nanofillers act as secondary reinforcement. The tensile, flexural and impact strengths of 10 wt% (combined alumina, silica and alumina tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Prakash et al [15] investigated the influence of microand nano-fillers on the mechanical properties of pultruded unidirectional glass fibre-reinforced epoxy composite systems and concluded that the improved mechanical properties indicate that the unidirectional glass fibre-reinforced epoxy with combined microand nanofiller-filled composite is a good candidate for structural application. Manjunath et al [16] studied the effect of filler content on the performance of epoxy/PTW composites and concluded that PTW additions showed beneficiary effects on the density, hardness, and stiffness properties of composites; however, strength properties and ductility were found to decrease with the increasing content of PTW. Finally, Sudheer et al [17] gave a general review of epoxy composites and particularly on ceria epoxy nanocomposites.…”
Section: The Influence Of Micro-and Nano-filler Content On the Mechanmentioning
confidence: 99%
“…Prakash et al [15] investigated the influence of microand nano-fillers on the mechanical properties of pultruded unidirectional glass fibre-reinforced epoxy composite systems and concluded that the improved mechanical properties indicate that the unidirectional glass fibre-reinforced epoxy with combined microand nanofiller-filled composite is a good candidate for structural application. Manjunath et al [16] studied the effect of filler content on the performance of epoxy/PTW composites and concluded that PTW additions showed beneficiary effects on the density, hardness, and stiffness properties of composites; however, strength properties and ductility were found to decrease with the increasing content of PTW. Finally, Sudheer et al [17] gave a general review of epoxy composites and particularly on ceria epoxy nanocomposites.…”
Section: The Influence Of Micro-and Nano-filler Content On the Mechanmentioning
confidence: 99%
“…[ 12 ] In this regard, polymer‐based nanocomposites have been studied by many researchers. [ 13–17 ] In these studies, different types of nanofiller materials, wt% of nanofiller, and fabrication techniques were used. It was concluded that addition of nanofiller improves the mechanical properties of polymer based composites.…”
Section: Introductionmentioning
confidence: 99%
“…SLCEP acts as a soft fiber, increasing the energy consumption. Manjunath et.al . reported unidirectional glass fiber reinforced epoxy composites filled with nano‐alumina, silica and micro‐alumina trihydrate.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the poor thermal conductivity of epoxy resin hinders its application in the field of electronic packaging . Various nanoparticles (such as nano‐alumina, nano‐silica, nano‐titanium dioxide, etc.) have been added into epoxy resin to improve the mechanical property, thermal conductivity, dielectric property and wear resistance by researchers.…”
Section: Introductionmentioning
confidence: 99%